The Effect of Agricultural Wages, Land Area, Mechanization, and Manufacturing Wages on Labor Absorption in the Agricultural Sector in Indonesia - Rahmadani, Citra; Sakti, Rachmad Kresna (Journal of Development Economic and Social Studies, 2026)
This study aims to analyze the influence of agricultural sector wages, agricultural land area, agricultural mechanization, and manufacturing sector wages on labor absorption in the agricultural sector in Indonesia. This research uses secondary data with panel data regression analysis methods thru multiple linear regression techniques. Data were obtained from the Central Bureau of Statistics (BPS) and the Ministry of Agriculture, with and observation period from 2020-2024 using 34 provinces in Indonesia, and were processed using E-Views 10 software. The results of this study indicate that agricultural sector wages and agricultural land area have a positive and significant impact on labor absorption in the agricultural sector. Conversely, manufacturing sector wages have a negative and significant impact, reflecting a shift in labor from the agricultural sector to the manufacturing sector. Meanwhile, agricultural mechanization had a negative but non-significant impact on labor absorption in the agricultural sector, indicating that technology utilization was not yet optimal. These findings have implication for wage policies and agricultural land management, which play an important role in maintaining the sustainability of the agricultural workforce, as well as the need for technology development that is more adaptable to the characteristics of the agricultural workforce in Indonesia.